Leukocyte profile of IPB D1 chickens possessing the TLR4 gene following Salmonella Enteritidis infection - Susanti, Fitria; Murtini, Sri; Wibawan, I Wayan Teguh (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: IPB D1 chicken is a crossbreed developed by crossing local Indonesian chickens-Pelung, Sentul, and Kampung-with commercial broilers. This crossbreeding initiative led by researchers from the Faculty of Animal Science at IPB University, aims to develop a meat-type chicken breed that is well adapted to traditional backyard farming systems commonly found in rural areas.Materials and Methods: The objective of this study was to evaluate the resistance of IPB D1 chickens carrying the Toll-like receptor 4 (TLR4) gene against Salmonella enterica serovar Enteritidis. A total of 11 chickens were used in this experiment. Detection of the TLR4 gene was conducted using Polymerase Chain Reaction (PCR) and sequencing techniques, followed by assessment of the chickens' immune response through total and differential leukocyte counts.Results: The results showed that IPB D1 chickens with the TLR4-positive genotypes (GG and AG) exhibited stronger immune responses and more stable leukocyte profiles compared to TLR4-negative chickens (AA genotype) following exposure to S. Enteritidis. These findings suggest that the TLR4 gene plays an important role in innate immunity and may enhance resistance to bacterial infection.Conclusion: Overall, this study highlights the potential of IPB D1 chickens as a resilient local breed suited for sustainable poultry farming, particularly in resource limited environments.Keywords: IPB D1 chickens, leukocyte profile, non-specific immune response, Salmonella Enteritidis, TLR4 gene